Prices for Crop and Livestock Cost-Return Budgets - Langemeier, Larry N.; Jones, Rodney (My University, 1995)
A publication detailing wheat, corn, grain sorghum, and soybean price projections.
MF1013_1995-10
Keywords: MF1013; Economics; Crops; MF